GANGGUAN IMUNODEFISIENSI PRIMER (PID) - kusumo, pratiwi (MAJALAH ILMIAH WIDYA, 2012)
Primary Immunodeficiency Disease (PID) is rare disorder in adult NS most often serious forms are detected during infancy orchildhood. Recently the incidents of PID are increasing, that we have to be aware especially to the children. The objective of thiswriting is to discuss the Primary immunodeficiency disorder (PIDs) which are broadly classified as disorders of adaptive immunity(i.e.,T-cell, B-cell or combined immunodeficiencies) or of innate immunity (e.g. phagocyte and complement disorders) and usuallyattacts the children. The method used library research and the data are analized descriptively. It can be concluded that: (1) Althoughthe clinical manifestations of PIDs are highly variable, most disorders involve at least an increased susceptibility to infection. (2) Thefailure to thrive; poor response to prolonged use of antibiotics; persistent thrush or skin abscesses; or a family history of PID (3) Theapplication of mutation analysis is becoming an integral part of the complete evaluation of patients with primary immunodefiency (4)PIDs should be suspected in patients with: recurrent sinus or ear infections or pneumonias within a 1 year period.